Low-Dimensional Materials and Devices 2019 2019
DOI: 10.1117/12.2529209
|View full text |Cite
|
Sign up to set email alerts
|

Strong-field-driven dynamics and high-harmonic generation in interacting 1D systems (Conference Presentation)

Abstract: The observation of high-order harmonic generation (HHG) from bulk crystals is stimulating substantial efforts to understand the involved mechanisms and their analogue to the intuitive three-step recollision model of gas phase HHG. On the technological side, efficient solid-state HHG is anticipated to enable compact attosecond and ultraviolet light sources that could unveil electron dynamics in chemical reactions and provide sharper tomographic imaging of molecular orbitals. Here we explore the roles of electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…Therefore, one can expect substantial changes of the HHG yield due to modifications of the band gap. This fact has recently raised interest among theoretical works on the use of doped materials for the HHG [26][27][28][29] . For instance, the effect of impurity levels on the HHG is discussed in the theoretical investigations exploiting time-dependent density functional theory 27 , where the authors have shown the enhanced HHG yield from the donor-doped material due to the electron tunneling from the impurity states to the conduction band.…”
Section: B Hhg From Solids With Defectsmentioning
confidence: 99%
“…Therefore, one can expect substantial changes of the HHG yield due to modifications of the band gap. This fact has recently raised interest among theoretical works on the use of doped materials for the HHG [26][27][28][29] . For instance, the effect of impurity levels on the HHG is discussed in the theoretical investigations exploiting time-dependent density functional theory 27 , where the authors have shown the enhanced HHG yield from the donor-doped material due to the electron tunneling from the impurity states to the conduction band.…”
Section: B Hhg From Solids With Defectsmentioning
confidence: 99%